Outcomes of Atrioesophageal Fistula Following Catheter Ablation of Atrial Fibrillation Treated with Surgical Repair versus Esophageal Stenting. (10th March 2014) - MOHANTY, SANGHAMITRA; SANTANGELI, PASQUALE; MOHANTY, PRASANT; BIASE, LUIGI DI; TRIVEDI, CHINTAN; BAI, RONG; HORTON, RODNEY; BURKHARDT, J. DAVID; SANCHEZ, JAVIER E.; ZAGRODZKY, JASON; BAILEY, SHANE; GALLINGHOUSE, JOSEPH G.; et al.
Management of Atrioesophageal Fistula Post‐AF Ablation Introduction Atrioesophageal fistula (AEF) is a rare but devastating complication of radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF). Surgical repair and esophageal stents are available treatment options for AEF. We report outcomes of these 2 management strategies. Methods Nine patients with AEF post‐RFCA for AF were included in this study. AEF was diagnosed based on symptoms and chest CT imaging. Of the 9 patients, 5 received stents and 4 underwent surgical repair of fistula. Results AF ablation was performed under general anesthesia (n = 4) or conscious sedation (n = 5). During ablation, RF power was maintained between 25 and 35 Watts in areas close to the esophagus and energy delivery discontinued when esophageal temperature reached 38 °C. Seven patients underwent ablation with 3.5‐mm open‐irrigated catheter, 1 with 8‐mm nonirrigated catheter, and 1 had surgical epicardial ablation. Seven patients received proton pump inhibitor and sucralfate before and after procedure. AEF symptoms developed within 2–6 weeks from ablation. Esophageal stenting was performed in 5 patients (median age 58 years, median time from RFCA 4 weeks) and 4 underwent surgical repair (median age 54 years, median time from RFCA 4 weeks) within 2–4 hours from diagnosis. All 5 patients receiving stents died within 1 week of the procedure due to cerebral embolism, septic shock, or respiratory failure. On the other hand, the 4 patients that received surgical repair were alive at median follow‐up of 2.1 years (P = 0.005). Conclusions Esophageal stenting should be discouraged and prompt surgical repair is crucial for survival in patients with atrioesophageal fistula.